Unlocking the Potential of Programming Education: Enhancing Conceptual Understanding and Student Engagement with Sphero SPRK Robot - Ibrahim Nnass; Juan-Carlos Muñoz; Michael A. Cowling; Roger Hadgraft (Journal of Pure & Applied Sciences, 2023)
This research investigates the use of the 'Sphero SPRK+' robot as a programming assistant to enhance conceptual understanding and engagement in programming education. The research addresses the challenges of teaching programming and underlines the significance of students understanding programming structures, semantics, syntax and planning. The Sphero robot offers multiple programming options, including graphic blocks, a pictorial command line, and text commands, catering to diverse learning styles. The approach of the study is based on a cognitive learning model, with the Sphero robot providing immediate feedback throughout practising. The experiment incorporates two groups: one using Blocks and the other using JavaScript code with Sphero's assistance. Results suggest that using Sphero SPRK robot enhances programming learning outcomes, particularly for novice learners. Participants express satisfaction with the engaging and practical learning experience, favouring the ease of Blocks for learning programming logic. The study provides significance for educational settings and emphasises the value of robotics and block-based programming in promoting algorithmic thinking and computational skills.